Kesiapan Merespon terhadap Aspek Negatif dan Positif Dampak Globalisasi Dalam Pendidikan Islam - Erwin Muslimin; Deden Heri; Mohamad Erihadiana (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
The purpose of this research is to find out the ability of the Indonesian nation to respond to globalization: readiness to respond to the negative and positive aspects of the impact of globalization. This type of research is Library Research, namely research through literature or literature studies. Sources of data in this study are primary data, namely books that directly discuss the ability of the Indonesian nation to respond to globalization. The data analysis technique used to obtain conclusions is descriptive qualitative by emphasizing deductive conclusions, namely how to draw conclusions from general to specific things. The conclusion of this paper is that the final conclusion in this study is that the Indonesian nation in responding to the negative and positive aspects of the impact of globalization, should be addressed proportionally because this is a good attitude as a reflection of moderate Islam. Meanwhile, the hard efforts to face the era of globalization must be that the Indonesian nation must be able to produce quality human resources, and have the ability that includes behavior, hard work, discipline, trustworthy responsibility and the like guided by the teachings of AI-Qur'an and Hadith